2019
DOI: 10.3389/fmicb.2019.01985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sample Preparation Methods for Fast Proteotyping of Microorganisms by Tandem Mass Spectrometry

Abstract: Tandem mass spectrometry-based proteotyping allows characterizing microorganisms in terms of taxonomy and is becoming an important tool for investigating microbial diversity from several ecosystems. Fast and automatable sample preparation for obtaining peptide pools amenable to tandem mass spectrometry is necessary for enabling proteotyping as a high-throughput method. First, the protocol to increase the yield of lysis of several representative bacterial and eukaryotic microorganisms was optimized by using a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 46 publications
4
71
1
Order By: Relevance
“…The literature is becoming rich in alternative sample preparation protocols for MS-based proteomics. For example, we recently proposed a proteotyping assay based on SP3 magnetic beads for protein purification and digestion in roughly 30 min (31). Being easily adapted to 96-well plates and robotization, SP3based digestion is the method of choice for quick, high-throughput, and highly reproducible proteome digestions, as recently demonstrated (20,32).…”
Section: Discussionmentioning
confidence: 99%
“…The literature is becoming rich in alternative sample preparation protocols for MS-based proteomics. For example, we recently proposed a proteotyping assay based on SP3 magnetic beads for protein purification and digestion in roughly 30 min (31). Being easily adapted to 96-well plates and robotization, SP3based digestion is the method of choice for quick, high-throughput, and highly reproducible proteome digestions, as recently demonstrated (20,32).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this issue, Pible et al [ 19 ] recently described an analytical approach based on the phylopeptidomics signature, a concept through which the number of peptides shared between organisms can be predicted to allow quantification of the relative biomasses of microorganisms in a given sample. Protocols for rapid preparation of bacterial peptides have been proposed to make proteotyping applicable when screening isolates [ 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of SW480 colon cancer cell lysates using S‐Trap technology identified 4662 proteins compared with 3981 proteins identified using a traditional in‐solution method and 4278 using filter‐aided sample preparation (FASP) . In a comparative study, SP3 yielded 1835 proteins compared with 1483 identified using S‐Trap in cell lysates where processing times were significantly lower in SP3 (28 min) than in S‐Trap and in‐gel digestion (115 and 206 min, respectively). A recent protein preparation method called protein aggregation capture (PAC) allowed identification of low‐abundance proteins including cytokines Csf3 and Cxcl10 in cell lysates .…”
Section: Resultsmentioning
confidence: 99%